Strategies for sustainable livelihoods of shallot picking workers households in Brebes Regency - Muhammad Fauzan; Gordius Woltman Tuga (Institute of Computer Science (IOCS), 2023)
This study aims to analyze the income of shallot-picking workers and their contribution to the total household income and to identify the strategies of the shallot-picking workers to achieve sustainable livelihoods. This study used primary data from a survey of 45 respondents using a questionnaire and was analyzed descriptively. The results showed that the income of shallot-picking workers in Brebes Regency was classified as significant towards total household income. This shows that picking workers depends on their livelihood from this job. Household strategies to support the achievement of sustainable livelihoods were included in the accumulation strategy. Increasing the welfare of extracted workers can be done by increasing productive activities